Leadership styles, instructional leadership practices and teachers’ job performance amongst administrators at high-performing vocational schools in Jakarta, Indonesia / Dita Puruwita Gunadi - Gunadi, Dita Puruwita (2024)
Leadership is the bedrock of the success of any organization. These studies have established leadership to be the critical element that contributes to effective organizational output, including Job Performance. In view of the 21st challenging era, investigation on best practices amongst administrators in High-Performing Vocational Schools is paramount. In view of this, this study aims to explore the relationship between Leadership Styles (LS) and Instructional Leadership practices (IL) and teachers’ Job Performance (JP) amongst administrators at High-Performing Vocational Schools in Jakarta, Indonesia. This study was guided by eight research objectives and eight research questions. A mixed-methods was employed to explore the relationships between LS, IL practices and JP. Inferential statistics were employed to analyse quantitative findings and thematic analysis was employed to analyse the qualitative findings. Instrumentation developed by Bass & Avolio, Hallinger, Hanif, Ali & Haider were adapted and modified to gather the quantitative data. Meanwhile, qualitative data was collected through a set of open-ended questions and semi-structured interviews to complement the triangulation process in this study. The sample of the study consisted of 155 administrators and 375 teachers from 23 High-Performing Vocational Schools in Jakarta, Indonesia. Findings indicated that most administrators rated themselves as Transformational leaders as this was corroborated by the teachers. Secondly, the administrators rated themselves practising a high level of IL, which was corroborated by the teachers.